ECO-LABELLING OF ACCOMMODATION FACILITIES AND ITS PERCEPTION BY RURAL TOURISTS: CASE STUDY OF VOJVODINA - Bradić, Milan; Kosar, Ljiljana; Djeri, Lukrecija; Vukosav, Svetlana; Garača, Vuk (Economics of Agriculture, 2017)
With transportation, hotel industry eco-efficiency forms the basis of the eco-efficiency in tourism operations. Although the tourism industry is a huge consumer, very few studies has been published on energy saving and renewables in terms of stakeholders attitudes on the topic. One of the ultimate goals of sustainable development is to foster responsible environmental behaviour not only for tourism operators, but also for tourists themselves. This paper represents the results of qualitative and quantitative research that was conducted in 59 accommodation facilities in rural areas of Vojvodina. The main task of the research was to explore possibilities of improving the environmental aspects of environmental responsible consumer behaviour in the hospitality industry. The aim of the research is to improve the tourism and hospitality market participants understanding of the relationship between positive consumer environmental protection attitude and responsibility with business standards in hospitality industry in rural areas. The research findings show the nature of such relationships.